Materiales compuestos cementicios reforzados con tejidos de fibra natural aplicados en estructuras de hormigón armado, estudio de revisión - Benítez Soxo, Walther Israel (2022)
Advances in civil engineering involve one of the materials used in construction, since the main objective of these changes is to improve their characteristics and properties. To achieve these changes, it comes to the study of reinforcing compounds that help the structural elements. These composite materials have the necessary sustainability in their production to guarantee a low environmental impact. In this study, a bibliographical review about the NFRCM compounds was carried out. The types of composites were studied, focusing on cementitious matrix composites, vegetable reinforcing fibers and their characteristics. The elaboration processes of these composite materials were reviewed, as well as the placement techniques, their properties and interaction reinforcing reinforced concrete elements and finally their possible uses. In this investigation we will focus on the reinforcements in the form of bidirectional fabrics orthogonally embedded in the matrix. The results of this type of reinforcement compounds are positive, providing the elements with better characteristics against external forces. The behavior of these compounds depends largely on the interaction at the matrix-textile reinforcement and NFRCM compound-reinforced concrete element interfaces.